DISCOVERY AND CORE LEARNING MODEL TOWARD CREATIVE THINKING VIEWED FROM LOGICAL MATHEMATICAL INTELLIGENCE - Veronika Yusnita Andriani Prastika; Riyadi Riyadi; Siswanto Siswanto (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research aims to 1) which learning model that supports students’ creative thinking ability whether discovery, CORE, or conventional learning model, 2) which model that supports creative thinking ability the most to high, moderate, and low level students, 3) know if there is interaction between learning model and students’ logical mathematical intelligence, and creative thinking ability. This is a quasi-experimental research with the population of eighth graders of junior high schools in Madiun Regency. The research design used a group pretest-posttest control design. The sample was determined using stratified cluster random sampling. This research uses two-way unequal ANOVA. This research concluded that 1) students’ creative thinking skill is developed better using Discovery than CORE and conventional learning model, 2) students with high logical mathematical intelligence have higher creative thinking ability than those with moderate and low logical mathematical intelligence,3) there is no interaction between learning model and logical mathematical intelligence with creative thinking ability.Keywords: Creative Thinking; Learning Model; Logical Mathematical Intelligence. AbstrakTujuan dari penelitan ini untuk mengetahui 1) model pembelajaran manakah yang memberikan kemampuan berpikir kreatif yang lebih antara model pembelajaran discovery learning, CORE atau konvensional, 2) manakah yang memberikan kemampuan berpikir kreatif yang lebih baik siswa yang memiliki kecerdasan logis matematis tinggi, sedang, atau rendah, 3) apakah terdapat interaksi antara model pembelajaran dan keceredasan logis matematis dengan kemampuan berpikir kreatif siswa. Metode yang digunakan pada penelitian adalah eksperimen semu, dengan populasi siswa kelas VIII SMP N Se-Kabupaten Madiun. Desain penelitian menggunakan group pretest-posttest control design Pemilihan sampel dengan menggunakan stratified cluster random sampling. Teknik analisis penelitian ini menggunakan anava dua jalan dengan sel tak sama. Kesimpulan pada penelitian ini 1) kemampuan berpikir kreatif siswa yang kenai model discovery learning lebih baik daripada model pembelajaran CORE dan konvensional, 2) Kemampuan berpikir kreatif siswa yang memiliki kecerdasan logis matematis tinggi lebih baik daripada siswa yang memiliki kecerdasan logis matematis sedang dan rendah, , 3) tidak ada interaksi antara model pembelajaran dan kecerdasan logis matematis dengan kemampuan berpikir kreatif.Kata kunci: Berpikir kreatif; kecerdasan logis matematis; model pembelajaran.